Development and Properties of High Density Polyethylene (HDPE) and Ethylene‐Vinyl Acetate Copolymer (EVA) Blend Antioxidant Active Packaging Films Containing Quercetin. (18th November 2014) - Han, Tian‐tian; Lu, Li‐xin; Ge, Changfeng
<x xml:space="preserve">Abstract</x> The antioxidant quercetin was incorporated into high density polyethylene (HDPE) and ethylene‐vinyl acetate copolymer (EVA) films by flat compression. The mass ratio of HDPE : EVA was 65 : 35, and the amount of quercetin in the films was 0.74% (wt%) and 1.23%, respectively. The method of manufacturing the films achieved a high quercetin retention rate. The addition of quercetin did not significantly modify the thermal stability or the oxygen barrier of the films, while the water vapour barrier was weakened to some extent. Release of quercetin from the active antioxidant films into 50% ethanol (simulant for high alcohol containing products and milk as well as some dairy products) and 95% ethanol (simulant for fatty foods) at 37°C was periodically measured by HPLC over 45 days. The diffusion of antioxidant followed Fick's law. In 50 and 95% ethanol, the release content of quercetin was 70 and 10%, respectively, the diffusion coefficient (D) was 10−13 and 10−15 m2/s, and the partition coefficient (K) was 44 and 5863, respectively. The films showed a good release profile and could be used for the protection of foods. Copyright © 2014 John Wiley & Sons, Ltd.